Local government and intergovernmental fiscal relations in Nigeria and Brazil a comparative study - Olowu, Dele (1980)
There are striking similarities between two developing countries, Brazil and Nigeria, not only in terms of political and economic institutions but also in terms of their attempts to reform the structure and management of their respective local government systems. There are indications of recent attempts by the Nigerian federal government to borrow from its Brazilian counterpart in order to bring about reforms of its local government structure and operations. The effects of these reforms were appraised in terms of the management of intergovernmental relations Finally, the two countries' local government systems are examined and suggestions are given by which they can mutually benefit from each other's experience.
Keywords: Management of local government -- Brazil; Management of local government -- Nigeria; Local governance; Constitutional reform